An Examination of Cooperative and Collaborative Learning Strategies in the Teaching of Islamic Religious Education - Ihsan. HS, Muh. Nur; U, Usman; Qaddafi, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the nature, principles, and procedures of cooperative and collaborative learning strategies, as well as their relevance to the development of 21st-century skills in Islamic Religious Education (PAI). The method used is library research with a descriptive-analytical approach through a review of books, journals, and related research findings. The results indicate that cooperative learning emphasizes teamwork in small groups with positive interdependence, while collaborative learning focuses on the co-construction of knowledge through interaction and reflection. Both strategies are grounded in social constructivism, humanistic theory, and connectivism, which align with Islamic values such as ta‘?wun (mutual assistance), sy?r? (consultation), and ukhuwah (brotherhood). The implementation of these strategies has proven effective in enhancing students’ critical thinking, communication, collaboration, and creativity (4C), while simultaneously strengthening Islamic character formation. Therefore, cooperative and collaborative learning strategies represent relevant and transformative approaches to addressing the challenges of PAI learning in the era of the Merdeka Curriculum and the 21st century.